Hypothetical molecular interconnection between type 2 diabetes and dyslexia - Bulbul, Tugba; Baharlooie, Maryam; Safaeinejad, Zahra; Gure, Ali Osmay; Ghaedi, Kamran (BMC, 2021)
Background Dyslexia is one of the most common learning disabilities, especially among children. Type 2 diabetes is a metabolic disorder that affects a large population globally, with metabolic disorders. There have been several genes that are identified as causes of Dyslexia, and in recent studies, it has been found out that some of those genes are also involved in several metabolic pathways. For several years, it has been known that type 2 diabetes causes several neurodegenerative disorders, such as Alzheimer's disease and Parkinson's disease. Furthermore, in several studies, it was suggested that type 2 diabetes also has some associations with learning disabilities. This raises the question of whether ``Is there a connection between type 2 diabetes and dyslexia?{''}. In this study, this question is elaborated by linking their developmental processes via bioinformatics analysis about these two diseases individually and collectively. Result The literature review for dyslexia and type two diabetes was completed. As the result of this literature review, the genes that are associated to type 2 diabetes and dyslexia were identified. The biological pathways of dyslexia, and dyslexia associated genes, type 2 diabetes, and type 2 diabetes associated genes were identified. The association of these genes, regarding to their association with pathways were analysed, and using STRING database the gene associations were analysed and identified. Conclusion The findings of this research included the interaction analysis via gene association, co-expression and protein-protein interaction. These findings clarified the interconnection between dyslexia and type 2 diabetes in molecular level and it will be the beginning of an answer regarding to the relationship between T2D and dyslexia. Finally, by improving the understanding this paper aims to open the way for the possible future approach to examine this hypothesis.
Keywords: Dyslexia; T2D; Hyperglycaemia; WNT signalling; Primary cilia; DCDC2; ROBO1; CTNNB1